Successful Development of a Fetal Ovine Model for Esophagus Tissue Engineering - Amulya K Saxena; Herwig Ainoedhofer; Piotr Soltysiak (EL-Med-Pub, 2018)
In esophagus tissue engineering, large animal models need to be developed to generate tissues of substantive size that can be applied in the future for clinical applications. The ovine fetal model has been successfully developed in this pilot study for esophagus tissue generation. Fetus (n = 5) was operated between the 120 and 125 days of gestation (term 140 days) with a longitudinal neck incision through which the esophagus was exposed. Full-thickness esophagus biopsies were obtained after which an end-to-end anastomosis was performed. Organoid units isolated from biopsies were seeded on collagen scaffolds to create tubular constructs which were implanted into the fetal omentum. The fetuses were returned and the pregnancy continued. There was no mortality and all five lambs were delivered at term. "Rudimentary" tissue engineered esophagus was generated using the omentum as an in situ bioreactor. The ovine fetal model for esophagus tissue engineering could successfully be established in this pilot study.